DEVELOPMENNT OF A MULTI-CRITERIA DECISION FRAMEWORK FOR COAL FIRED POWER PLANT EMISSION CONTROL TECHNOLOGY SELECTION - Rahmayani, Vita
Coal-fired power plants produce pollutants that are harmful to the environment, including SO2 and NOx. The regulation of the Ministry of Environment Number P.15/MENLHK/SETJEN/KUM.1/4/2019 on emission standards for thermal power plants sets limits for SO2 and NOx with a lower limit of 200 mg/NM3